Some aspects of black sigatoka epidemiology in Central America and outlook for future research in Sub-Saharan Africa - Gauhl, F. (1994)
Airborne asco-and conidiospores of Mycosphaerella fijiensis, the causal agent of black sigatoka, were trapped in the Atlantic lowland of Costa Rica, Central America, during two consecutive years. Selected environmental parameters were monitored in a heavily infected plantation of the False Horn cultivar Currare (Musa sp., AAB group). Ascospore release was related to rainfall. Even rainfall of 0.1mm, which was the smallest amount to be registered, resulted in ascospore release. Ascospore dispersal was low in the cooler seasons and high in the warmer season of the year. This indicates the inhibitory influences of lower temperatures.